IDENTIFIKASI GEJALA SERANGAN HAMA DAN PENYAKIT PADA TANAMAN ANGGREK - Muliani, Sri; Ridwan, Andi; syatrawati, Syatrawati; Nildayanti, Nildayanti; Alferi, Yusri; Parando, Chindy Loda (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2024)
Rian Orchid is an orchid garden that has a collection of various types of orchids in Tondobakaru Village, Mamasa Regency. One of the factors that hinders the growth of cultivated orchids is the presence of pests and diseases. The research was carried out with the aim of identifying symptoms of pest and disease attacks that usually attack orchid plant collections. The method used in this research was direct observation and interviews with orchid garden owners, then the data obtained was analyzed descriptively qualitatively. Observation results showed that there were 4 types of pests, namely whiteflies (Bemecia tabaci), mealybugs, elephant beetles (Orchidaphillus atherrimus) and leaf-eating beetles. Meanwhile, there were 3 types of disease symptoms found, namely Bacterial soft and brown rot, Bacterial Brown Spot, and Anthracnose.